147 Burden of Undiagnosed Hypertension in Sub-Saharan Africa: A Systematic Review and Meta-Analysis. (6th June 2015) - Ataklte, Feven; Erqou, Sebhat; Kaptoge, Stephen
Abstract : The burden of hypertension in Sub-Saharan Africa has been increasing over the past few decades. However, a large proportion of the population with hypertension remains undiagnosed, untreated, or inadequately treated, contributing to the rising burden of cardiovascular disease in the region. We conducted a systematic review and meta-analysis to assess the recent burden of hypertension in Sub-Saharan Africa, based on studies published between 2000 and 2013. We pooled data from 33 surveys involving over 110 414 participants of mean age 40 years. Hypertension prevalence varied widely across the studies (range 15%–70%), partly because of differences in participant mean ages (31–76 years). The predicted prevalence of hypertension at mean participant ages of 30, 40, 50, and 60 years were 16%, 26%, 35%, and 44%, respectively, with a pooled prevalence of 30% (95% confidence interval, 27%–34%). Of those with hypertension, only between 7% and 56% (pooled prevalence: 27%; 95% confidence interval, 23%–31%) were aware of their hypertensive status before the surveys. Overall, 18% (95% confidence interval, 14%–22%) of individuals with hypertension were receiving treatment across the studies, and only 7% (95% confidence interval, 5%–8%) had controlled blood pressure. This review found a high prevalence of hypertension, as well as low percentage of hypertension awareness, treatment, and control in Sub-Saharan Africa, highlighting the need for implementation of timely and appropriate strategies for diagnosis, control, and prevention.